Association of food parenting practice patterns with obesogenic dietary intake in Hispanic/Latino youth: Results from the Hispanic Community Children's Health Study/Study of Latino Youth (SOL Youth). (1st September 2019) - LeCroy, Madison N.; Siega-Riz, Anna Maria; Albrecht, Sandra S.; Ward, Dianne S.; Cai, Jianwen; Perreira, Krista M.; Isasi, Carmen R.; Mossavar-Rahmani, Yasmin; Gallo, Linda C.; Castañeda, Sheila F.; Stevens, June
Abstract: Some food parenting practices (FPPs) are associated with obesogenic dietary intake in non-Hispanic youth, but studies in Hispanics/Latinos are limited. We examined how FPPs relate to obesogenic dietary intake using cross-sectional data from 1214 Hispanic/Latino 8-16-year-olds and their parents/caregivers in the Hispanic Community Children's Health Study/Study of Latino Youth (SOL Youth). Diet was assessed with 2 24-h dietary recalls. Obesogenic items were snack foods, sweets, and high-sugar beverages. Three FPPs (Rules and Limits, Monitoring, and Pressure to Eat) derived from the Parenting strategies for Eating and Activity Scale (PEAS) were assessed. K-means cluster analysis identified 5 groups of parents with similar FPP scores. Survey-weighted multiple logistic regression examined associations of cluster membership with diet. Parents in the controlling (high scores for all FPPs) vs. indulgent (low scores for all FPPs) cluster had a 1.75 (95% CI: 1.02, 3.03) times higher odds of having children with high obesogenic dietary intake. Among parents of 12–16-year-olds, membership in the pressuring (high Pressure to Eat, low Rules and Limits and Monitoring scores) vs. indulgent cluster was associated with a 2.96 (95% CI: 1.51, 5.80) times greater odds of high obesogenic dietary intake. All other associations were null. Future longitudinal examinations of FPPs are needed to determine temporal associations with obesogenic dietary intake in Hispanic/Latino youth.